OTIMIZAÇÃO DA EXTRAÇÃO DE POLIFENÓIS DE RESÍDUOS DE VINIFICAÇÃO PARA O DESENVOLVIMENTO DE LIPOSSOMAS - Montagner, Giane Engel (2020)
Winemaking residues, also known as marc, are mixtures of seeds and grape skins that are produced during the winemaking process. These residues, normally discarded by the industry, can be used, because during the production of the wine, only a fraction of the grape's polyphenols is transferred to the wine, remaining around 70% in the marc. However, polyphenols have low stability and consequently low bioavailability. Nanoencapsulation can contribute to the improvement of these factors, where a promising delivery system for phenolic compounds, contained in marc, is the liposomes, which are spherical vesicles composed of a lipid bilayer with a polar medium, such as water. The objective of the study was to optimize the polyphenol extraction technique of vinification residues to produce, characterize and evaluate the stability of liposomes containing grape seed extract, aiming at choosing a stable formulation. For this purpose, grape seed was first defined as the raw material, as it is the part with the most phenolic compounds in the residue and consequently more antioxidant activity. Afterwards, the process of extracting polyphenols from the seed was optimized, through the Full-Fraction Design experimental design. Thus, the best extraction condition was when 1.7 g of seed, 33% of grain alcohol and 15 minutes of extraction were used. The extract was nanostructured in liposome dispersions, using the reverse phase evaporation method at a concentration of 1 mg / mL. The formulations produced were maintained in three different conditions: room temperature (RT) (25 ± 2 ºC), refrigeration (RE) (4 ± 2 ºC) and climatic chamber (CC) (40 ºC + 75% RH) in glass bottles amber. In order to verify the behavior and evaluate the stability of the formulations, it was taken into account the average diameter, the polydispersity index, the pH, catechin content and the organoleptic characteristics, such as color, odor and general appearance. The prepared liposomes had a diameter of 238.6 nm, PDI 0.252, zeta potential -14.66 mV, pH 5.71 and catechin content of 1.10%. Parameters kept stable, when subjected to refrigeration, for 30 days. Under ambient temperature and climatic chamber conditions, stability was not maintained. The liposomes were evaluated at different pHs and remained stable at pHs found in the mouth and stomach, already at intestinal pH, there was an increase in the size of the particles and preservation of the catechin content, thus indicating a possible beginning of breakdown of the nanostructure and intestinal uptake. The incorporation of the polyphenols contained in the grape seed, by liposome, proved to be effective, thus concluding that the liposome is a viable system for the protection of polyphenols.